ANALYSIS OF SIR EPIDEMIOLOGICAL MODELOF INFLUENZA: INSIGHTS INTO THE FUTURE OF H1N1 (International Journal of Engineering Sciences & Management Research, 2016)
Review of the literature of influenza modeling studies and discussed how these models can provide insights into the future of the currently circulating novel strain of influenza A (H1N1), earlier known as swine flu. The fact how the feasibility of controlling an epidemic critically depends on the value of basic reproduction number , have been discussed. The for novel influenza A (H1N1) has recently been estimated to be between 1.4 and 1.6, which is below the values of estimated for the year 1918-19 pandemic strain(mean , range 1.4 to 2.8) and is comparable to values estimated for seasonal strain(mean , range 0.9 to 2.1). A recent modeling study has shown a global cooperative strategy is essential in order to control a pandemic. It is also been shown that by modeling cross-species transmission it may be possible to predict the emergency of pandemic strains of influenza.